The importance of leadership in performance management in Lesotho's ministry of the public service - Mosaase, Sefora Mahape (My University, 2018)
In 2001, the government of Lesotho introduced a new system to monitor and evaluate public servants’ performance. The Performance Management System (PMS) was also introduced to implement national plans effectively so as to pave the way for performance related pay system. This was done to address issues of accountability and improved service delivery. For ease of facilitation of implementation, Directors of Human Resources (DHRs) were deployed across all ministries of the Lesotho government. This study shows that DHRs were not given necessary support by ministerial leadership from the different ministries as a result, PMS was not implemented as envisaged by the Ministry of the Public Service as the mother ministry. A Performance Management System (PMS) is explained as a tool to monitor and evaluate employees’ performance. PMS could also be seen as a tool to facilitate faster decision making, and adoption of a corrective act aligning employees’ performance with an organisation’s strategies and goals in a more effective and efficient manner (Walser et al., 2013). PMS can be used in government entities or in the private sector as a tool for monitoring and evaluating performance. This research aimed to determine the importance of leadership in PMS implementation as well as the strategies used to implement the system. The study was undertaken using a qualitative research methodology. A descriptive case study design was used and semi-structured questions were developed to administer face to face interviews. As implementers of the system, the Human Resources Directors deployed across the ministries by the Ministry of the Public Service were interviewed. The results highlighted that the implementers used a combination of leadership styles as a strategy to facilitate a robust and reliable PMS. They also used meetings and training workshops to disseminate information about PMS across all ministries. The results also underlined a lack of ownership from ministerial leadership and non-compliance with the terms and references of PMS by Head of Departments. Though it is evident that the level of awareness about PMS is very high among employees in the Government of Lesotho, there also exists an attitude of resistance of adopting PMS, as a result, the system has not been implemented effectively. The PMS policy is still in draft form therefore leadership in line ministries is reluctant to adopt PMS without a guiding document. Consequently, the system has not been implemented effectively, because other employees do not take Public Service Rules and Regulation as not providing enough guidance.
A research report submitted to the Faculty of Law Commerce and Management, University of the Witwatersrand, in 50% fulfilment of the requirements for the degree of Master of Management (in the field of Public Sector Monitoring and Evaluation). February, 2018
Keywords: Performance--Management; Performance standards--Lesotho